Green biotechnology for valorisation of residual biomasses in nutraceutic sector: Characterization and extraction of bioactive compounds from grape pomace and evaluation of the protective effects in vitro. Issue 2 (17th January 2021) - Messina, Concetta Maria; Manuguerra, Simona; Catalano, Giuseppe; Arena, Rosaria; Cocchi, Massimo; Morghese, Maria; Montenegro, Lucia; Santulli, Andrea
Abstract: The grape pomace (GP) is an important by-product of winemaking, accounting for about 13-25% of the grapes processed. The aim of this work was to investigate the nutritional and antioxidant composition of GP obtained from Nero d'Avola (NA) grape, one of the most important indigenous varieties in Italy, in order to verify application in nutraceutics. Seeds and skin of the GP were studied for their nutritional and antioxidants composition, fatty acid and polyphenols profile, bioactives properties in vitro, by gravimetric, spectrophotometric and chromatographic techniques. The results showed that NAGP seeds are rich in the beneficial polyunsaturated fatty acids and that the polyphenols extracted from the GP skin present a strong antiradical and antiproliferative activity, attested also in vitro, in human skin fibroblast (HS-68) and in hepatoma cell line (Hep-G2). Obtained results underline the possibility to employ this residual biomass for nutraceuticals application, contributing also to increase the sustainability. Graphical Abstract: